Manajemen Pembelajaran Kitab Kuning di Madrasah Miftahul Huda Pondok Pesantren Darul Huda - Bastria Anas Saputra (Pascasarjana IAIN Ponorogo, 2023)
Based on the researcher's findings about the management of the yellow book learning at Madrasah Miftahul Huda, first: planning for the yellow book learning is done by compiling the curriculum, syllabus, and learning schedule. In determining the curriculum and syllabus, it is not much different from the previous year, while the list of lessons is formulated in the agenda of the teacher council meeting at the beginning of each semester. Second: the organization of learning is carried out by ustaz and students after the formation of a learning schedule with the distribution of materials and class divisions that have been determined for each level. Third: the implementation of the yellow book learning is carried out by all ustadz by delivering the yellow book learning material including fiqh, morals, tool science (nahwu and shorof). As for the method used, namely the bandongan method, lectures. Fourth: the evaluation of the yellow book learning is carried out at the end of each semester. The evaluation includes oral and written exams that discuss the subject matter for the past semester. The purpose of this research is to know the management of the yellow book learning at Madrasah Miftahul Huda. Several statements indicate that: the learning in Miftahul Huda Madrasah is felt to be very influential and effective as an addition to knowledge about the teachings of Islam. The implication of this yellow book learning has a significant impact on students during the learning process, both the impact of competence and changes in student behavior.